The Effectiveness of Duration Skin to Skin Contact and Telelactation in Exclusive Breastfeeding for Postpartum Mothers in Tangerang - Novita, Regina Vidya Trias; Utami, Tuti Asrianti; Marni, Nursanty Wardoyo; Yusandra, Evra (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Skin to Skin Contact (SSC) immediately after birth (SSC), proved could initiate breastfeeding for the first time. Sustaining breastfeeding could stop because the mother cannot be fencing their problems, and the end to stop to breastfeed their baby. the telelaction was a solution for mothers with difficulties during lactation with support during pandemics. The aim analysis the characteristic (age, education level, type of birth, and parity), duration of SSC, and telelactation to exclusive breastfeeding during two weeks at home. Methodquasi-experimental design, one group posttest-only. Analysis independent T-test, and regression logistic binary among102 respondents with accidental sampling. The results are the majority of mothers age 20-35 (85.3%), Have the highest level of education (93.1%), spontaneous delivery (65.7%), and multipara (69.6%). Duration SSC 31-60 minutes (64.7%) active telelactation (83.3%) at least twice during two weeks and (72.5%) have breastfeeding exclusively. SSC less than 30 minutes positively 16 times and SSC 30 minutes have 26.7 times to exclusive breastfeeding. Parity, duration SSC, and telelactation significant to Exclusive breastfeeding (p less than 0.05).Regression logistics was found parity (pvalue 0.036), duration SSC?30 minutes (pvalue 0.005) and telelactation (pvalue 0.014). SSC less than 30 minutes 4 times, parity 3 times, and telelactation 4 times influence mothers to exclusive breastfeeding during two weeks at home. The competency of the health professional should be increased and the telelactation was one of the alternative to apply a continuum of care for postpartum mothers who want to breastfeed, with health protocol during the pandemic.